Tantangan dan Strategi Pemasaran UMKM di Era Teknologi dan Digitalisasi - Dariz Radyananda Barus; Handika Natanael Simamora; Michael Glora Surya Sihombing; Josua Panjaitan; Lenti Susana Saragih (Journal of Creative Student Research, 2023)
The research uses a library study method which prioritizes literature review. This research was created with the aim of finding out the challenges and strategies in developing MSME businesses in the era of technological progress and digitalization. Digitalization is currently very important for MSME entrepreneurs, because increasingly advanced technology opens up great opportunities for MSME entrepreneurs to develop their business. However, even though there has been much progress, there are still challenges that MSMEs must face regarding the development of digitalization. Through the digital era, MSME marketing strategies and systems must be able to utilize their potential to the maximum extent possible in order to compete and develop sustainably. Manufacturers are getting closer to the daily lives of their consumers through contemporary marketing strategies in the current era of digitalization. Digital media strategy is a good choice because the marketing channel chain will get shorter. Since market control can be measured by share ownership, businesses should maintain share ownership as one of their strategies. An ineffective business strategy will result in losses for the business.